Herausforderungen und Handlungsstrategien armer Familien im Kontext europäischen Strukturwandels - Staab, Philipp (European Journal of Mental Health, 2015)
Challenges for Poor Families and Their Strategies for Action in the Context of the Structural Transformation of Europe: An intensification of social inequality can be observed in several countries of the European Union. As a result, poverty has become a key concept of the EU’s social policy agenda. Because of family members’ commitment to unconditional mutual solidarity, families are considered to be an important bulwark in the war on poverty. Poor families, however, are unable to fulfil such expectations. Their daily lives, as well as the family itself as an institution, are marked by pressures resulting from institutional transformations of labour markets and the welfare state. This contribution outlines the specific challenges that poor families face and describes three typical strategies of coping with poverty within the family. While routinisation and intensification strategies are only moderately successful in improving the family situation, seeking options is a strategy that opens up new opportunities, which also offers entry points for providing social aid and services.